Evaluación del comportamiento en poscosecha de la cebolla roja (allium cepa l.) en atmósferas modificadas y dos temperaturas de almacenamiento Latacunga – Cotopaxi 2015 - Ortiz López, Darwin Vinicio (2015)
The red onion (Allium cepa L). It is native to Asia, it is a source of minerals iron, phosphorus and vitamins A and C also increases the ability to dissolve blood clots internally, thereby preventing coronary thrombosis. In Ecuador producers lose twenty to forty percent of its production after harvest, because the onion has ninety percent of his compassion is water is dehydrated. In 2015 production is seven hundred thousand metric tons. The research is focused on reducing post harvest losses for increasing the profitability of producers, this research was performed at the Experimental Center of Agricultural Sciences at the Technical University of Cotopaxi, located in the parish Salache low, Latacunga Canton province Cotopaxi, located at an altitude of 2,780 meters, here are two factors that were evaluated: storage temperatures, atmospheres modified in a plot design divided twice for the Tukey significance test was used at 5%. In order to achieve these objectives, the following variables were analyzed: weight, pH, electrical conductivity, percentage of sprouting of the results obtained, we conclude that onion can be maintained without weight loss, the pH is maintained so ensures that the product has some level of degradation, it is checked with statistical data that chemical reactions and physiological processes remains with the monitoring of electrical conductivity. Using T10 c2t2a1 treatment (without curing + 4 °C + rollpack) to keep the weight of the product and its quality. Traditional onion harvest no cure to stop the process from the beginning of harvest weight loss caused by exposure to sol. Preservar onion bulbs at a temperature of 4 ° C to reduce the normal physiological processes that degrade the quality.